Ethnopharmacology, Chemical Composition and Pharmacological Activity of Amethyst Sea Holly (Eryngium amethystinum L) - Duran, Mladen; Suručić, Relja; Tubić, Biljana; Škrbić, Ranko (Scripta Medica, 2025)
Eryngium amethystinum L is a plant which grows in Balkan and Apennine peninsulas. The aerial parts, roots and fruits are used in ethnopharmacology of Italy and Western Balkan countries. Traditional preparations of E amethystinum were used in treatment of oedema, malaria and gastrointestinal diseases. Essential oils and extracts were isolated from aerial parts and roots of E amethystinum and examined by antimicrobial, antioxidative and cytotoxic assays. Gas-chromatography analysis showed predominance of germacrene D and spathulenol in essential oils of E amethystinum aerial parts, which have contributed to strong cytotoxic activity, while the methanolic extract exhibited strong antioxidative and antimicrobial activity. This article summarises all existing knowledge regarding E amethystinum, its chemical composition and pharmacological activity.
Keywords: Eryngium amethystinum; Essential oils; Anti-infective agents; Oxidative stress; Cytotoxic activity